Computing resource and work allocations using social profiles - Lavin, Peter; Kenny, Eamonn; Coghlan, Brian A. (Wydawnictwa AGH, 2013)
If several distributed and disparate computer resources exist, many of which have been created for different and diverse reasons, and several large scale computing challenges also exist with similar diversity in their backgrounds, then one problem which arises in trying to assemble enough of these resources to address such challenges is the need to align and accommodate the different motivations and objectives which may lie behind the existence of both the resources and the challenges. Software agents are offered as a mainstream technology for modelling the types of collaborations and relationships needed to do this. As an initial step towards forming such relationships, agents need a mechanism to consider social and economic backgrounds. This paper explores addressing social and economic differences using a combination of textual descriptions known as social profiles and search engine technology, both of which are integrated into an agent technology.
Computer Science
Bibliogr. s. 291-293.
Keywords: agents; search; resource allocation; social; economic; Social Grid Agents; social profile